2008
DOI: 10.1007/s12013-008-9039-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dealing with DNA Damage-Induced Replication Problems

Abstract: During every S phase, cells need to duplicate their genomes so that both daughter cells inherit complete copies of genetic information. Given the large size of mammalian genomes and the required precision of DNA replication, genome duplication requires highly fine-tuned corrective and quality control processes. A major threat to the accuracy and efficiency of DNA synthesis is the presence of DNA lesions, caused by both endogenous and exogenous damaging agents. Replicative DNA polymerases, which carry out the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
120
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 121 publications
0
120
0
Order By: Relevance
“…Thus, it remains unclear how RAD51C differentially regulate short tract gene conversions and LTGC. HR plays a major role in the repair of DNA lesions associated with replication and in the recovery of stalled/collapsed replication forks (7,9,17,46). RAD51C-deficient cells were hypersensitive to genotoxic agents that induce genome-wide DSBs and DSGs, indicating the critical role of RAD51C in HR function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it remains unclear how RAD51C differentially regulate short tract gene conversions and LTGC. HR plays a major role in the repair of DNA lesions associated with replication and in the recovery of stalled/collapsed replication forks (7,9,17,46). RAD51C-deficient cells were hypersensitive to genotoxic agents that induce genome-wide DSBs and DSGs, indicating the critical role of RAD51C in HR function.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, RAD51C-deficient cells also displayed chromatidtype errors, providing evidence that RAD51C is a novel component in the FA and BRCA pathway of DNA repair. BRCA pathway also plays a critical role in the repair of genome-wide DSBs and DSGs that arise during replication (7,9,26). The BRCA proteins BRCA1, BRCA2, and PALB2 have been shown to regulate intra-S-phase checkpoint (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now compelling evidence that HR plays an essential role in the repair of DSBs that arise during DNA replication, even in the absence of exogenous DNA damage (13,33). The increased sensitivity of hPos4-depleted cells to a PARP inhibitor that causes DSBs in a replication-dependent manner and the defect in the repair of site-specific DSBs by HR in these cells provide strong evidence that the hPso4 complex participates in the repair of replicationassociated DSBs via a homology-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using inhibitors of ATR and CHK1 reported that the abundance of ssDNA during replication stress exhausts the available pool of RPA increasing the likelihood that unprotected ssDNA will be cleaved by endonucleases (13). Stalled forks are believed to be repaired primarily, but not exclusively, by homologous recombination (14,15). The resulting DNA structure intermediates generated during homologous recombination repair (HRR; i.e., Holliday junctions) are cleaved by endonucleases such as MUS81/EME1 yielding a doublestranded break.…”
Section: Introductionmentioning
confidence: 99%